DESAIN BUSANA PELINDUNG DIRI UNTUK PROFESI MAKE UP ARTIST - Putri Marganing Utami; Sri Wening; Emy Budiastuti (Jurnal Da Moda, 2022)
The Covid-19 pandemic has an impact on make-up artists (MUA) who work as facial make up and hair styling for various interests that are at high risk of exposure to Covid-19 transmission so that they need personal protective clothing to avoid droplets. Based on this, researchers developed personal protective clothing designs for the make up artist profession to identify criteria, steps, and opinions of design experts about the feasibility of personal protective clothing design for the make up artist profession. Referring to the research model written by Thiagarajaan (1974) with 4D steps on the subject of make up artist research in bantul area obtained: (1) Design criteria using waterproof materials, washable, inconspicuous colors, leeway can be arranged, closed and tight, and in accordance with the needs of the make up artist profession. (2) The define stage is obtained from literature studies and interviews of prospective users, design is used to pour the ideas obtained, the development stage of researchers reordering product design according to input from design experts and disseminate introducing products to prospective users. (3) The results of personal protective clothing design assessment for the make up artist profession are very high category of 3 respondents or 100% so that the design is worthy to be disseminated to prospective users. Pandemi Covid-19 berdampak terhadap make-up artist (MUA) yang berprofesi sebagai perias wajah dan menata rambut untuk berbagai kepentingan yang berisiko tinggi terpapar penularan Covid-19 sehingga membutuhkan busana pelindung diri agar terhindar dari droplet. Berdasarkan hal tersebut peneliti mengembangkan desain busana pelindung diri untuk profesi make up artist untuk mengidentifikasi kriteria, langkah-langkah, dan pendapat ahli desain tentang kelayakan desain busana pelindung diri untuk profesi make up artist. Mengacu pada model research yang ditulis oleh Thiagarajaan (1974) dengan langkah 4D pada subjek penelitian make up artist di daerah Bantul didapatkan: (1) Kriteria desain menggunakan bahan anti air, bisa dicuci, warna tidak mencolok, kelonggaran bisa diatur, tertutup dan rapat, dan sesuai dengan kebutuhan profesi make up artist. (2) Tahapan define diperoleh dari study literatur dan wawancara calon pengguna, design digunakan untuk menuangkan ide-ide yang didapat, tahap development peneliti menyusun kembali desain produk sesuai masukan dari para ahli desain dan disseminate mengenalkan produk kepada calon pengguna. (3) Hasil penilaian desain busana pelindung diri untuk profesi make up artist berkategori sangat tinggi dari 3 orang responden atau 100% sehingga desain tersebut layak untuk didesiminasikan kepada calon pengguna.